A microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611105608.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-30
AI Technical Summary
①固有的磁诱导团聚与比表面积限制:常规工艺制备的ZnFe2O4材料通常具有较高的结晶度,在热力学驱动下极易发生磁性团聚,导致其比表面积大幅减小,活性位点被深度包埋
本发明通过低温煅烧精准调控ZnFe2O4尖晶石的结晶度,其低结晶度性质打破晶格长程有序性,在表面暴露出丰富的配位不饱和铁活性位点,作为与过一硫酸盐(PMS)结合与活化位点;同时,该低结晶度ZnFe2O4具有优异的介电和磁损耗双重电磁响应特性,微波吸收效应强,能在微波辐照下于非均相界面快速激发局域电磁场及“微观热点”,充分发挥微波的热效应与非热效应。在微波与该催化剂的协同作用下,体系能高效活化过一硫酸盐产生多组分活性物种,实现对水体中有机污染物的高效降解,多次循环后催化剂仍保持较高稳定性,且支持煅烧再生。
Smart Images

Figure CN122999206A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave water treatment and remediation technology, and in particular to a microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst, its preparation method, and its application. Background Technology
[0002] With increasingly frequent industrial manufacturing and agricultural activities, large quantities of toxic and persistent organic pollutants are being discharged into aquatic ecosystems, posing a significant threat to human health and ecological stability. Imidacloprid (IMI), a typical representative of first-generation neonicotinoid insecticides, has been classified as a typical emerging high-risk pollutant due to its high water solubility, significant leaching, and environmental persistence. Traditional water treatment methods (such as biological and physical adsorption methods) are insufficient to completely mineralize it, easily resulting in pollutant residues. Therefore, developing efficient, green, and sustainable advanced treatment technologies has become a critical bottleneck issue that urgently needs to be addressed in the current water treatment field.
[0003] In recent years, advanced oxidation processes (AOPs) based on persulfate (PMS) have been criticized for generating sulfate radicals (SO42-). - With advantages such as high redox potential and high yield, it shows broad application prospects in the treatment of recalcitrant organic wastewater. To accelerate PMS activation, the physical energy of electromagnetic waves (such as microwaves) has gradually become a research hotspot. Microwaves (MW) possess unique physical effects such as rapid penetration of reaction media, selective heating, and localized energy transfer. However, existing homogeneous microwave / persulfate systems suffer from inherent defects in practical applications, including extremely high energy consumption and low oxidant utilization. Furthermore, the selective heating and rapid interfacial energy transfer characteristics of microwaves lack effective "absorbers" and "conversion carriers" in homogeneous systems, leading to a significant waste of microwave energy.
[0004] Therefore, the introduction of heterogeneous catalysts has attracted widespread attention. Among them, spinel ferrite (ZnFe2O4) has shown potential in absorbing microwave energy and forming local "hot spots" on its surface due to its inherent magnetic loss and dielectric properties. In particular, ZnFe2O4, as a representative material, has been attempted for use in microwave-assisted heterogeneous systems. However, existing ZnFe2O4 catalysts have the following shortcomings in preparation and application: ① Inherent magnetically induced agglomeration and specific surface area limitation: ZnFe2O4 materials prepared by conventional processes usually have high crystallinity and are prone to magnetic agglomeration under thermodynamic drive, resulting in a significant reduction in their specific surface area and deep embedding of active sites.
[0005] ② Insufficient exposure of surface active sites: The traditional highly crystalline spinel structure is too compact and has a complete lattice, lacking defect structures, resulting in an extremely low density of effective metal sites at the interface for binding with PMS and electron transfer.
[0006] ③ Low microwave energy-chemical energy conversion efficiency: High-crystallinity materials have limited dielectric loss and unsaturated polarization centers, making it difficult to excite high-density microwave localization effects under microwave irradiation.
[0007] Therefore, how to overcome material agglomeration while controlling its microstructure through simple and efficient methods, fundamentally changing the material's crystallinity to induce a large number of active sites to be exposed, and significantly improving its microwave absorption and conversion capabilities, is a major challenge for the industrial application of this technology. Summary of the Invention
[0008] The purpose of this invention is to provide a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst, its preparation method, and its application, in order to solve the above-mentioned technical problems.
[0009] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst, comprising the following steps: 1) Mix zinc chloride, ferric chloride, and water to obtain a mixed solution; 2) The mixed solution is heated in a water bath, and then an alkaline solution is added to carry out a precipitation reaction; 3) The obtained precipitate was washed until neutral and then dried, followed by calcination to obtain a microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst.
[0010] Furthermore, the molar ratio of zinc chloride to ferric chloride is 1:1~3, and the Zn in the mixed solution... 2+ The concentration is 0.04~0.06 mol / L.
[0011] Furthermore, the water bath heating temperature is 80~95℃, and the precipitation reaction time is 1~3h.
[0012] Furthermore, the alkaline solution is a sodium hydroxide solution with a concentration of 1-2M.
[0013] Furthermore, the drying temperature is 70~90℃, and the drying time is 6~10h.
[0014] Furthermore, the calcination temperature is 150~250℃, the calcination time is 1~3h, and the heating rate is 1~10℃ / min.
[0015] The present invention also provides a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst prepared by the above preparation method.
[0016] This invention also provides an application of a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst in the treatment of organic pollutants in water, comprising the following steps: Microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst was added to water containing organic pollutants, followed by the addition of persulfate. The reaction was then carried out under microwave irradiation to catalytically degrade the organic pollutants.
[0017] Furthermore, the organic pollutants include one or more of imidacloprid, pentachlorophenol, chlorpyrifos, malathion, phoxim, dimethoate, bisphenol A, diclofenac sodium, sulfamethoxazole, phenol, 4-chlorophenol, and atrazine.
[0018] Furthermore, the amount of microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst added is 0.1~0.4 g / L, the amount of persulfate added is 0.1~0.4 g / L, the microwave irradiation is in constant temperature mode with a temperature range of 30~60℃, and the pH of the water is 5.5~6.0.
[0019] The beneficial effects of this invention are: This invention precisely controls the crystallinity of ZnFe2O4 spinel through low-temperature calcination. Its low crystallinity breaks the long-range lattice order, exposing abundant coordinated unsaturated iron active sites on the surface, serving as binding and activation sites for permonosulfate (PMS). Simultaneously, this low-crystallinity ZnFe2O4 exhibits excellent dual electromagnetic response characteristics in terms of dielectric and magnetic loss, with strong microwave absorption. Under microwave irradiation, it can rapidly excite local electromagnetic fields and "microscopic hot spots" at heterogeneous interfaces, fully utilizing the thermal and non-thermal effects of microwaves. Under the synergistic effect of microwaves and this catalyst, the system can efficiently activate permonosulfate to generate multi-component active species, achieving efficient degradation of organic pollutants in water. The catalyst maintains high stability even after multiple cycles and supports calcination regeneration.
[0020] The catalyst preparation method provided by this invention is simple and rapid, has good stability and can be recycled. The microwave treatment process is convenient to operate and is suitable for the end-of-pipe deep treatment of various industrial pesticide wastewater, pharmaceutical wastewater and chemical recalcitrant organic wastewater. Attached Figure Description
[0021] Figure 1 The XRD pattern of ZnFe2O4 spinel prepared in Example 1 of this invention; Figure 2 Transmission electron microscopy image of ZnFe2O4 spinel prepared in Example 1 of this invention; Figure 3 Three-dimensional images of the reflection loss of ZnFe2O4 spinel with different thicknesses prepared in Example 1 of the present invention; Figure 4 The diagram shows the cyclic performance of microwave / ZnFe2O4 spinel-activated PMS for the degradation of imidacloprid in Example 2 of this invention. Figure 5 This is a graph showing the performance of microwave / ZnFe2O4 spinel-activated PMS in degrading various organic pollutants in Example 3 of the present invention. Detailed Implementation
[0022] This invention provides a method for preparing a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst, comprising the following steps: 1) Mix zinc chloride, ferric chloride, and water to obtain a mixed solution; 2) The mixed solution is heated in a water bath, and then an alkaline solution is added to carry out a precipitation reaction; 3) The obtained precipitate was washed until neutral and then dried, followed by calcination to obtain a microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst.
[0023] In this invention, the molar ratio of zinc chloride to ferric chloride is 1:1 to 3, preferably 1:2; the Zn in the mixed solution... 2+ The concentration is 0.04~0.06 mol / L, preferably 0.05 mol / L.
[0024] In this invention, the water bath heating temperature is 80~95℃, preferably 85~92℃, and more preferably 90℃; the precipitation reaction time is 1~3h, preferably 1~2h.
[0025] In this invention, the alkaline solution is a sodium hydroxide solution with a concentration of 1-2 M, preferably 1.2-1.6 M, and more preferably 1.4 M.
[0026] In this invention, the drying temperature is 70~90℃, preferably 75~85℃, and more preferably 80℃; the drying time is 6~10h, preferably 7~9h, and more preferably 8h.
[0027] In this invention, the calcination temperature is 150~250℃, preferably 180~220℃, and more preferably 200℃; the calcination time is 1~3h, preferably 2h; and the heating rate is 1~10℃ / min, preferably 2~8℃ / min, and more preferably 5℃ / min.
[0028] The present invention also provides a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst prepared by the above preparation method.
[0029] This invention also provides an application of a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst in the treatment of organic pollutants in water, comprising the following steps: Microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst was added to water containing organic pollutants, followed by the addition of persulfate. The reaction was then carried out under microwave irradiation to catalytically degrade the organic pollutants.
[0030] In this invention, the organic pollutants include one or more of imidacloprid, pentachlorophenol, chlorpyrifos, malathion, phoxim, dimethoate, bisphenol A, diclofenac sodium, sulfamethoxazole, phenol, 4-chlorophenol, and atrazine.
[0031] In this invention, the amount of microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst added is 0.1~0.4 g / L, preferably 0.2~0.3 g / L; the amount of persulfate added is 0.1~0.4 g / L, preferably 0.2~0.3 g / L; the microwave irradiation is in a constant temperature mode, with a temperature range of 30~60℃, preferably 40~50℃, and more preferably 45℃; the pH of the water is 5.5~6.0, preferably 5.8.
[0032] In the microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst prepared by this invention, Zn / Fe occupy tetrahedral and octahedral sites in the spinel structure, respectively. The low crystallinity of this ZnFe2O4 spinel catalyst exposes a large number of coordinated unsaturated iron sites, which serve as binding sites for persulfate. At the same time, the prepared ZnFe2O4 has excellent dielectric properties and strong microwave absorption effect, thereby significantly improving catalytic activity.
[0033] The microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst provided by this invention can rapidly and efficiently activate persulfate to generate active species under microwave irradiation. It can achieve complete degradation of neonicotinoid insecticide imidacloprid within 30 minutes. Cyclic experiments show that the provided microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst can maintain high activity after multiple uses and can be regenerated by calcination.
[0034] The microwave / ZnFe2O4 spinel / PMS treatment technology provided by this invention can effectively degrade and remove various organic pollutants, including chlorpyrifos, 4-chlorophenol, and bisphenol A, from polluted water.
[0035] Reaction pathway analysis: Quenching experiments, probe experiments, and electron spin resonance spectroscopy results using methanol, tert-butanol, p-benzoquinone, furfuryl alcohol, and dimethyl sulfoxide as quenchers were conducted to determine the presence of sulfate radicals, high-valence iron species, and singlet oxygen in the system. Therefore, this catalytic system degrades pollutants through a dual pathway of free radicals and non-free radicals.
[0036] Catalytic Mechanism Analysis: The highly efficient catalytic degradation of pollutants by the microwave / ZnFe2O4 spinel / PMS system proposed in this invention stems from a deep synergistic mechanism between the catalyst's excellent microwave absorption performance and the exposure of coordinated unsaturated iron sites caused by low crystallinity. Firstly, the low-crystallinity spinel lattice structure breaks long-range order, exposing a large number of coordinated unsaturated iron sites on its surface, which act as active sites and undergo surface complexation with PMS. Secondly, ZnFe2O4 spinel possesses excellent dielectric and magnetic loss characteristics, rapidly converting electromagnetic energy into thermal and non-thermal energy under microwave irradiation, inducing "hot spots" at the catalytic interface and promoting molecular polarization, thus accelerating the interfacial electron transfer rate. Simultaneously, Zn sites exert an "electron pump" effect through the Zn-O-Fe bridging network, dynamically replenishing electrons lost from Fe sites. Under dynamic electron balance, the system forms a radical pathway dominated by sulfate radicals and a non-radical pathway including high-valence iron species and singlet oxygen, achieving efficient degradation of various organic pollutants in wastewater.
[0037] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0038] Example 1
[0039] Preparation of microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst: 1) Add 5 mmol zinc chloride, 10 mmol ferric chloride hexahydrate, and 100 mL ultrapure water to a 250 mL three-necked round-bottom flask, dissolve and mix well to obtain a mixed solution; 2) Using a water bath heating method, heat the mixed solution to 90°C and reflux it; add 50 mL of 1.4 M sodium hydroxide solution dropwise to the above mixed solution; keep the reaction system at 90°C, reflux it, stir for 1 h, and then let it cool naturally to room temperature; 3) The obtained precipitate was centrifuged and washed until the pH of the supernatant after centrifugation was neutral. The supernatant was washed 3-5 times with ultrapure water and anhydrous ethanol, respectively. The centrifuged sample was dried in a high-temperature drying oven at 80℃ for 8h to obtain the ZnFe2O4 spinel precursor. The dried sample was calcined in a muffle furnace at 200℃ for 2h at a heating rate of 5℃ / min. The calcined sample is the target microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst.
[0040] The microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst prepared in Example 1 was characterized by XRD and TEM. Figure 1-2 Phase analysis results showed that the crystal phase of the prepared ZnFe2O4 spinel catalyst belonged to PDF#03-065-3111 (ZnFe2O4). TEM results showed that the prepared ZnFe2O4 spinel exhibited a rice-grain-like nanorod structure with an average length of about 100 nm.
[0041] The microwave-responsive, low-crystallinity ZnFe₂O₄ spinel catalyst prepared in Example 1 was digested, and its elemental composition was analyzed by inductively coupled plasma atomic emission spectrometry (ICP-AES). The results showed that the relative concentrations of Zn and Fe in the ZnFe₂O₄ spinel were 1:2.0. These results confirm the successful synthesis of spinel-phase ZnFe₂O₄.
[0042] The microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst prepared in Example 1 was characterized using a microwave vector grid. Figure 3 The ZnFe2O4 spinel exhibited the lowest RL value of -16.35dB at a frequency of 7.18GHz (thickness of 5mm), indicating that this low-crystallinity ZnFe2O4 spinel has good microwave absorption performance.
[0043] Example 2
[0044] Microwave-assisted activation of low-crystallinity ZnFe2O4 spinel to degrade imidacloprid by persulfate
[0045] 1. Imidacloprid Degradation: 15 mg of ZnFe₂O₄ spinel from Example 1 was weighed and dispersed in 50 mL of a 10 mg / L imidacloprid solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (PMS mass concentration: 15 g / L) was added. Simultaneously, a microwave was turned on to initiate the reaction at a constant temperature of 50 °C. Samples were taken periodically during the reaction. The reaction solution was filtered through a 0.22 μm filter and quenched with an equal volume of methanol. The concentration of imidacloprid was determined using high-performance liquid chromatography (HPLC). After the reaction, the ZnFe₂O₄ spinel catalyst was recovered by filtration, washed with ultrapure water, and dried in a 60 °C oven. The catalytic degradation experiment was then repeated, with each reaction lasting 30 min. The ZnFe₂O₄ spinel after the fifth catalytic reaction was collected, dried, and calcined at 200 °C for 2 h to regenerate the catalyst. The degradation experiment was then repeated.
[0046] Figure 4The graph shows the performance of microwave-assisted low-crystallinity ZnFe2O4 spinel-activated persulfate degradation of imidacloprid in Example 2 of this invention. It can be seen that the ZnFe2O4 spinel catalyst can still achieve a degradation rate of over 75% within 30 minutes after 5 cycles, and the catalyst can be regenerated by calcination. The above experimental results indicate that the microwave-assisted low-crystallinity ZnFe2O4 spinel catalyst exhibits excellent performance and high stability in degrading organic pollutants.
[0047] 2. Reaction Pathway Analysis: Using methanol, tert-butanol, p-benzoquinone, furfuryl alcohol, and dimethyl sulfoxide as quenchers for active species, the results showed that methanol significantly inhibited the degradation of imidacloprid, while tert-butanol had no significant inhibitory effect, indicating the presence of a large number of sulfate free radicals in the system. Simultaneously, EPR and probe experiments confirmed the presence of high-valent iron species and singlet oxygen species in the system. This indicates that the microwave-assisted degradation of imidacloprid by low-crystallinity ZnFe₂O₄ spinel-activated persulfate follows a predominantly radical pathway, accompanied by the catalytic oxidation of non-radical high-valent iron.
[0048] Example 3
[0049] Microwave-assisted activation of low-crystallinity ZnFe2O4 spinel to degrade different organic pollutants by persulfate
[0050] Degradation of pentachlorophenol: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L pentachlorophenol solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal amount of methanol. The concentration of pentachlorophenol was determined by high performance liquid chromatography.
[0051] Degradation of chlorpyrifos: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L chlorpyrifos solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal amount of methanol. The concentration of chlorpyrifos was determined by high performance liquid chromatography.
[0052] Degradation of malathion: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L malathion solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of malathion was determined by high performance liquid chromatography.
[0053] Degradation of phoxim: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L phoxim solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of phoxim was determined by high performance liquid chromatography.
[0054] Degradation of dimethoate: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L dimethoate solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of dimethoate was determined by high performance liquid chromatography.
[0055] Degradation of Bisphenol A: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L bisphenol A solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of bisphenol A was determined by high performance liquid chromatography.
[0056] Degradation of diclofenac sodium: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L diclofenac sodium solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal amount of methanol. The concentration of diclofenac sodium was determined by high performance liquid chromatography.
[0057] Degradation of sulfamethoxazole: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L sulfamethoxazole solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of sulfamethoxazole was determined by high performance liquid chromatography.
[0058] Phenol degradation: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L phenol solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal volume of methanol. The concentration of phenol was determined by high performance liquid chromatography.
[0059] Degradation of 4-chlorophenol: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L 4-chlorophenol solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal amount of methanol. The concentration of 4-chlorophenol was determined by high performance liquid chromatography.
[0060] Degradation of atrazine: 15 mg of ZnFe2O4 spinel from Example 1 was weighed and dispersed in 50 mL of 10 mg / L atrazine solution. After stirring for 5 min to reach adsorption equilibrium, 1 mL of persulfate solution (mass concentration: 15 g / L) was added. The microwave was turned on simultaneously to carry out the reaction at a constant temperature of 50 °C for 30 min. Samples were taken at regular intervals during the reaction. The reaction solution was filtered through a 0.22 μm filter membrane and quenched with an equal amount of methanol. The concentration of atrazine was determined by high performance liquid chromatography.
[0061] Figure 5This image shows the performance of microwave-assisted low-crystallinity ZnFe2O4 spinel-activated persulfate degradation of various organic pollutants in Example 3 of this invention. The catalytic system exhibits significant degradation capabilities for organic pollutants, with removal efficiencies exceeding 85% for most pollutants within 30 minutes. In particular, pentachlorophenol, bisphenol A, diclofenac sodium, sulfamethoxazole, and p-chlorophenol were almost completely degraded. Furthermore, these results indicate that the catalytic system possesses higher reactivity towards electron-rich compounds. These results fully demonstrate the broad applicability and promising application prospects of this system in the treatment of various pollutants.
[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst, characterized in that, Includes the following steps: 1) Mix zinc chloride, ferric chloride, and water to obtain a mixed solution; 2) The mixed solution is heated in a water bath, and then an alkaline solution is added to carry out a precipitation reaction; 3) The obtained precipitate was washed until neutral and then dried, followed by calcination to obtain a microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst.
2. The preparation method according to claim 1, characterized in that, The molar ratio of zinc chloride to ferric chloride is 1:1~3, and the Zn in the mixed solution... 2+ The concentration is 0.04~0.06 mol / L.
3. The preparation method according to claim 1 or 2, characterized in that, The water bath heating temperature is 80~95℃, and the precipitation reaction time is 1~3h.
4. The preparation method according to claim 1, characterized in that, The alkaline solution is a sodium hydroxide solution with a concentration of 1-2M.
5. The preparation method according to claim 1, 2, or 4, characterized in that, The drying temperature is 70~90℃, and the drying time is 6~10h.
6. The preparation method according to claim 5, characterized in that, The calcination temperature is 150~250℃, the calcination time is 1~3h, and the heating rate is 1~10℃ / min.
7. The microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst according to claim 7 in the treatment of organic pollutants in water, characterized in that, Includes the following steps: Microwave-responsive, low-crystallinity ZnFe2O4 spinel catalyst was added to water containing organic pollutants, followed by the addition of persulfate. The reaction was then carried out under microwave irradiation to catalytically degrade the organic pollutants.
9. The application according to claim 8, characterized in that, The organic pollutants include one or more of imidacloprid, pentachlorophenol, chlorpyrifos, malathion, phoxim, dimethoate, bisphenol A, diclofenac sodium, sulfamethoxazole, phenol, 4-chlorophenol, and atrazine.
10. The application according to claim 8 or 9, characterized in that, The amount of microwave-responsive low-crystallinity ZnFe2O4 spinel catalyst added is 0.1~0.4 g / L, the amount of persulfate added is 0.1~0.4 g / L, the microwave irradiation is in constant temperature mode with a temperature range of 30~60℃, and the pH of the water is 5.5~6.0.
